Prędkość propagacji fali dźwiękowej w pniach olszy czarnej Alnus glutinosa (L.) Gaertn. w zależności od temperatury - Orzechowski, Michał; Budniak, Piotr (Leśne Prace Badawcze, 2013)
The aim of this study was to determine how thermal conditions affect the speed of sound wave propagation, in trunks of living alder Alnus glutinosa (L.) Gaertn. trees. This method in practiced when diagnosing the presence of internal decay in standing trees. Field work was carried out four times at different temperatures (+13°C, +3°C, -7°C and -16°C) using an impulse hammer. There was a significant correlation between the thermal conditions and the speed of sound wave propagation. Therefore, temperature must be taken into account to correctly diagnose tree health and timber quality.